Contrasting intra versus interspecies DNA sequence variation for representatives of the Batrachospermales (Rhodophyta): Insights from a DNA barcoding approach - Sherwood, Alison R.; Vis, Morgan L.; Entwisle, Timothy J.; Necchi, Orlando [UNESP]; Presting, Gernot G. (Wiley-Blackwell, 2008)
Sixty-five accessions of the species-rich freshwater red algal order Batrachospermales were characterized through DNA sequencing of two regions: the mitochondrial cox1 gene (664 bp), which is proposed as the DNA barcode for red algae, and the UPA (universal plastid amplicon) marker (370 bp), which has been recently identified as a universally amplifying region of the plastid genome. upgma phenograms of both markers were consistent in their species-level relationships, although levels of sequence divergence were very different. Intraspecific variation of morphologically identified accessions for the cox1 gene ranged from 0 to 67 bp (divergences were highest for the two taxa with the greatest number of accessions; Batrachospermum helminthosum and Batrachospermum macrosporum); while in contrast, the more conserved universal plastid amplicon exhibited much lower intraspecific variation (generally 0-3 bp). Comparisons to previously published mitochondrial cox2-3 spacer sequences for B. helminthosum indicated that the cox1 gene and cox2-3 spacer were characterized by similar levels of sequence divergence, and phylogeographic patterns based on these two markers were consistent. The two taxa represented by the largest numbers of specimens (B. helminthosum and B. macrosporum) have cox1 intraspecific divergence values that are substantially higher than previously reported, but no morphological differences can be discerned at this time among the intraspecific groups revealed in the analyses. DNA barcode data, which are based on a short fragment of an organellar genome, need to be interpreted in conjunction with other taxonomic characters, and additional batrachospermalean taxa need to be analyzed in detail to be able to draw generalities regarding intraspecific variation in this order. Nevertheless, these analyses reveal a number of batrachospermalean taxa worthy of more detailed DNA barcode study, and it is predicted that such research will have a substantial effect on the taxonomy of species within the Batrachospermales in the future.
Keywords: Batrachospermales; cox1; cox2-3 spacer; DNA barcode; plastid 23S rRNA; species identification; UPA